Alteration of thiol-disulfide homeostasis in workers occupationally exposed to arsenic. Issue 2 (4th March 2018) - Büyükşekerci, Murat; Bal, Ceylan; Serkant, Utku; Gündüzöz, Meşide; Alışık, Murat; Tutkun, Engin; Yılmaz, Ömer Hınç
ABSTRACT: This study evaluates the redox state in occupationally arsenic-exposed workers ( n = 71) by assessing the dynamic serum thiol-disulfide homeostasis. We determined the serum thiol-disulfide homeostasis parameters of exposed workers and controls ( n = 43) using a novel automated colorimetric assay. Median urinary As and 8-isoprostane levels of exposed group were significantly higher than control group (16.40 μg/L vs 2μg/L, p < .001 and 2.28 ng/ml vs 0.54 ng/ml, p < .001, respectively). Disulfide level, disulfide/native thiol ratio, and disulfide/total thiol ratio were significantly higher in exposed group. The mean ceruloplasmine and myeloperoxidase activities of As-exposed group were significantly higher than control group (117.15 U/L vs 87.02 U/L, p = .035 and 148.53 U/L vs 97.75 U/L, p = .000, respectively). The median catalase activity did not differ in the two groups. Our findings revealed that As disrupts the thiol-disulfide homeostasis in favor of disulfide.